2023
DOI: 10.1002/cti2.1440
|View full text |Cite
|
Sign up to set email alerts
|

Human EGFRvIII chimeric antigen receptor T cells demonstrate favorable safety profile and curative responses in orthotopic glioblastoma

Abstract: Objectives Glioblastoma is a highly aggressive and fatal brain malignancy, and effective targeted therapies are required. The combination of standard treatments including surgery, chemotherapy and radiotherapy is not curative. Chimeric antigen receptor (CAR) T cells are known to cross the blood–brain barrier, mediating antitumor responses. A tumor‐expressed deletion mutant of the epidermal growth factor receptor (EGFRvIII) is a robust CAR T cell target in glioblastoma. Here, we show our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(91 reference statements)
0
2
0
Order By: Relevance
“… 53 Therefore, it can be used as a therapeutic target for glioblastoma. 54 The identification of tumor neoantigens broadens the range of potential targets for solid tumor therapies.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Therefore, it can be used as a therapeutic target for glioblastoma. 54 The identification of tumor neoantigens broadens the range of potential targets for solid tumor therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In a xenograft model of human GBM, GCT02 CAR-T cells rapidly eliminated tumour cells with decreased cytokines secretion ( 178 ). Further research demonstrated that GCT02 CAR-T exhibited highly specific EGFRvIII-targeting preclinical function ( 179 ). Therefore, such CAR approaches need further clinical investigations.…”
Section: Immunotherapymentioning
confidence: 99%